Prevalence of Vitamin D Deficiency and Its Associated Risk Factors among Pregnant Women in Sbea, Libya - Aisha Zaidi; Huda Al-Griw; Omran Algriany; Basma Altameme; Mohammed Sultan (Khalij-Libya Journal of Dental and Medical Research, 2024)
Vitamin D deficiency during pregnancy has been linked to various negative health outcomes for mothers, neonates, and children. Sun exposure behaviors and dietary habits are known to impact vitamin D status. However, there is limited observational data on these behaviors among pregnant women in Sbia town. This study aimed to assess the prevalence of vitamin D deficiency among pregnant women in a developed region of Libya and examine the association between sun exposure behaviors and serum vitamin D levels. A total of 144 healthy pregnant women participated in the study, completing a face-to-face questionnaire on knowledge about vitamin D and sunlight exposure behaviors. Serum concentrations of 25-hydroxyvitamin D (25(OH)D) were measured using an enzyme-linked immunoassay. The results showed that 34% of the participants had vitamin D deficiency (25(OH)D < 20 ng/mL), with 43.8% classified as severely deficient (25(OH)D < 10 ng/mL). Women with shorter durations of sun exposure had significantly lower 25(OH)D levels compared to those with longer durations (15 mins: 13.2 ± 6.9 ng/mL vs. 1 hr: 19.2 ± 11 ng/mL; P = 0.03). Additionally, women who covered most of their bodies except for their face and hands had lower 25(OH)D concentrations (13.2 ± 11.3 ng/mL) compared to those who exposed their face, arms, and legs to sunlight (27.6 ± 8.9 ng/mL; P = 0.01). These findings highlight the persistence of maternal vitamin D deficiency and insufficiency despite a sunny environment in a developed region of Libya. من المعروف أن التعرض لأشعة الشمس والعادات الغذائية تؤثر على نسبة فيتامين د. وقد تم ربط نقص فيتامين د أثناء الحمل بسلوكيات الامهات السلبية مما يؤثر نقصه على الام والجنين.ولهذا السبب تم دراسة هده السلوكيات بين النساء الحوامل في بلدة السبيعة .هدفت هذه الدراسة لتحديد مستويات فيتامين (د) في مصل الدم عند النساء الحوامل ومعرفة معدل انتشار نقصه, ومدى التعرض لأشعة الشمس. شاركت في هده الدراسة حوالي 144 امرأة حامل تتمتع بصحة جيدة، وأكملن الاستبيان شخصيا وجهة لوجه وكان الاستبيان حول معرفتهن بفيتامين د و سلوكيات التعرض لأشعة الشمس. تم قياس تراكيز 25-هيدروكسي فيتامين د (25(OH)D) في المصل باستخدام اختبار الامتصاص الإنزيمي المرتبط بالمناعة. وقد أظهرت النتائج أن 34% من المشاركات يعانين من نقص في فيتامين د اقل من 20 نانوغرام/مل، بينما 43.8% من النساء يعانين من نقص شديد اقل من 10نانوغرام/مل. كما اظهرت النتائج وجود انخفاض معنوي في مستوى فيتامين د لدى النساء الاتي يتعرضن لشمس لفترات قصيرة (15 دقيقة: 13.2 ± 6.9 نانوغرام/مل) مقارنة بالاواتي يتعرضن لفترات اطول ( ساعة واحدة: 19.2 ± 11 نانوغرام/مل؛ P = 0.03). بالإضافة إلى ذلك، كانت لدى النساء اللواتي كن يغطين معظم أجسادهن باستثناء الوجه واليدين مستويات 25(OH)D (13.2 ± 11.3 نانوغرام / مل) أقل مقارنة بالنساء اللواتي كانوا يعرضن وجوههن وأيديهن وأرجلهن لأشعة الشمس الشمس (27.6 ± 8.9 نانوغرام/ مل؛ P = 0.01) . تبرز هذه النتائج استمرار نقص فيتامين د وعدم كفاية عند النساء الحوامل على الرغم من البيئة المشمسة في منطقة متطورة من ليبيا.